Usulan Peningkatan Kinerja Masinis Dan Asisten Masinis Kereta Api Berdasarkan Metode Fatique Index Dan PSQI - Mela Ardeline; Revi Lasmita (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
In Indonesia, almost every year train accidents occur which result in casualties and considerable material losses. The factors that cause train accidents are human resources, facilities, infrastructure and environmental factors. The method used in this study is the measurement of the level of fatigue that occurs in machinists and assistant machinists using the fatigue index calculator and for measuring the quality of sleep whether good or not using the Pitsburgh sleep quality index questionnaire. Data collection is divided into two parts, namely the collection of working time data from machinists and assistant machinists to determine the level of fatigue and the collection of data from the distribution of questionnaires to determine sleep quality. Working time data is the schedule of machinists and assistant machinists every day which will then be calculated the level of fatigue using the fatigue index calculator. For the calculation of sleep quality, the Pitsburgh sleep quality questionnaire was distributed to 62 respondents. From the results of the calculation of the fatigue index calculator for machinists and assistant machinists every day, it is found that the fatigue index value varies for each day. This can also be seen from the results of the calculation of the standard deviation for 62 respondents which ranges between the value of 6 or 7. The results of the calculation of the sleep quality index showed that 84% of machinists and assistant machinists have a good sleep quality.